2012
DOI: 10.1111/jhn.12000
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the structured Satisfaction Questionnaire with Gastrostomy Feeding (SAGA‐8) for caregivers of children with gastrostomy tube nutritional support

Abstract: The SAGA-8 questionnaire has a high discriminatory power to assess the degree of satisfaction experienced by parents/caregivers of children with HEN by GT and, subsequently, the patients' wellbeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…The SAGA‐8 by Martinez‐Costa et al . () was used to assess caregivers' satisfaction with GT feedings in the home. Results revealed that 50% of caregivers ( n = 36) expressed a high degree of satisfaction with GT feedings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SAGA‐8 by Martinez‐Costa et al . () was used to assess caregivers' satisfaction with GT feedings in the home. Results revealed that 50% of caregivers ( n = 36) expressed a high degree of satisfaction with GT feedings.…”
Section: Resultsmentioning
confidence: 99%
“…A contact person at each association received a survey packet that included an online anonymous survey, comprised of the Satisfaction Questionnaire with Gastrostomy Feeding (SAGA‐8) and a set of supplementary questions. SAGA‐8 was developed to assess degree of satisfaction with GT feedings for caregivers (Martinez‐Costa et al ., ). Psychometric properties have been assessed and SAGA‐8 has established reliability (α = 0.764) and external validity (x 2 = 69.21; P = 0.001; Martinez‐Costa et al .).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall rate of disagreement was low; a third reviewer was requested for <5% of the screened articles. The majority of these articles (78%) were cohort studies, 5 23,44,53,65,71,74,80,81,83 systematic reviews (5%), 7,49,89,96,97 and controlled trials (5%). 22,28,48,55,91 The 5 systematic reviews performed analyses on 0 to 25 articles each.…”
Section: Identifi Cation Of Included Articlesmentioning
confidence: 99%
“…Physician B also educated the caregivers and the patients regarding the safe methods for IOET feeding and tube insertion. After 3 days, physician C conducted a satisfaction survey by administering the Satisfaction Questionnaire with Gastrostomy Feeding (SAGA-8) [1314] (Appendix 1) directly to the patients if they were fully conscious and were able to communicate clearly or to the caregivers. Physician B determined the reason(s) for cessation of tube feeding (if needed), time at which oral feeding became feasible, and occurrence of complications (diarrhea, aspiration pneumonia).…”
Section: Methodsmentioning
confidence: 99%